The impact of virtual laboratories on the academic performance of grade 12 learners in impulse and momentum - Tatira, Benjamin; Mshanelo, Thembelani (Edelweiss Applied Science and Technology, 2024)
Virtual laboratories (labs) have evolved as an important tool in the sciences, delivering interactive and engaging platforms for learners to conduct experiments and comprehend complex concepts without the limitations of physical resources. They are an emerging teaching tool that offers interactive and immersive experiences that improve comprehension of complicated scientific concepts. This study assesses the impact of virtual labs on the academic achievement of Grade 12 learners on the topic of impulse and momentum in physics. It uses a quasi-experimental methodology to compare the performance of learners who used virtual labs to those who learned in the prevailing theoretical settings. A pre-test and post-test were used to assess learners’ academic success, and surveys were used to gather learner feedback on the learning tool. Preliminary data analysis indicates a statistically significant improvement in the test scores of learners using virtual labs, corroborating earlier studies that highlight the advantages of technologically enhanced learning environments. Furthermore, qualitative feedback indicates that learners found virtual labs more interesting and accessible, resulting in a more conducive learning environment. This work adds to the expanding body of evidence supporting the use of virtual labs in science teaching, especially in resource-constrained contexts where traditional laboratory equipment is limited or non-existent. The implications for curriculum design and educational policy are examined, with a focus on the importance of investing in digital infrastructure to support innovative teaching approaches.